Transition to Service-Oriented Enterprise Architecture - Assmann, Martin; Engels, Gregor (Proceedings of the Second European Conference on Software Architecture (ECSA 2008), Paphos (Cyprus))
Enterprise Architecture (EA) has undergone many changes since the IT has found its way into enterprises. At the moment the Service-Oriented Architecture (SOA) is being hyped but has also gained some importance. Implementing SOA can have many implications for an enterprise, depending on how visionary the implemented architecture is. This paper provides the description of an enterprise architecture that is fully-fledged concerning service-orientation and points out the architectural challenges that have to be mastered with future research results.